Change Agent System in Lean Manufacturing Implementation for Business Sustainability - Nordin, Norani; Belal, H.M. (International Journal of Supply Chain Management, 2017)
This paper aims to propose a model of change agent system in lean manufacturing implementation to achieve organizational sustainability in terms of knowledge co-creation process with employees by changing their behavioural and mind-set thereby increase organizational performance. This study conducted multi-case design which contains more than a single case company viz., company A and company B are presented here. Results demonstrated with mentioned concept. Lean manufacturing accomplished by change agent system in manufacturing industry.  The mentioned system is a promising way to ensure the translating of lean concept and its implementation to all workers in the company, by this means company achieving lean manufacturing culture to offer desired services to customers. This research contributes to create strategic corporate ways to succeed in lean manufacturing implementation by making knowledgeable and skilled human resource with the integrating of change agent system that will ensure value creation and organizational sustainability. There have been few scientific studies and research done on the mechanism involved in the change agent in lean manufacturing implementation. Our proposed model of change agent system to translate lean manufacturing concept is original and unique in practical field.